Engulfment is required for cell competition. - Li, W.; Baker, N.E. (Cell, 2007)
Genetic mosaics that place cells in competition within tissues may model features of tissue repair and tumor development and may reveal mechanisms of growth regulation. In one example, normal cells eliminate "Minute" cells that have reduced ribosomal protein gene dose and grow at their expense, replacing the Minute cells within developing compartments. We describe genes that are required by wild-type cells to kill Minute neighbors in Drosophila. The engulfment genes draper, wasp, the phosphatidylserine receptor, mbc/dock180, and rac1 are needed in wild-type cells for the death of Minute neighbors, whose corpses are engulfed by wild-type cells. Wild-type cells can themselves be killed by cells with elevated engulfing activity. Thus engulfment genes act downstream of growth differences between cells to eliminate cells with reduced ribosomal gene dose.